The Use of Hybrid Energy Storage Devices for Balancing the Electricity Load Profile of Enterprises - A. A. Belsky; A. N. Skamyin; O. S. Vasilkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
In this article, the authors consider the possibility of using a hybrid energy storage system to even out the load profile of the enterprise. Solving the problem of rational use of energy storage taking into account the initial variable load schedule will significantly reduce not only the cost of electricity consumption by the enterprise, but also the costs of its production. Detailed characteristics  of  batteries  with  various  types  of  electrolytes  and  supercapacitors  are  given. A model of the active scheme of a hybrid electric energy storage system consisting of a lithium-ion battery and a supercapacitor unit with the corresponding characteristics is presented. The model was carried out by using the SimPowerSystems software in MatLab. During the simulation, the temperature and the aging effects and of the batteries were not taken into account. The selfdischarge parameter of the battery was also not presented. As a result of the simulation, discharge characteristics of supercapacitors and batteries were obtained based upon which the expediency of their combined use for leveling load profiles of various types was substantiated. The paper presents the results of the simulation of operating modes of a hybrid energy storage device, combining the advantages of two types of energy storage devices, as well as a diagram of delivered power to the network, corresponding to the specified parameters. The paper provides a mathematical description of the increasing power by hybrid storage system resulting from the combined use of supercapacitors and batteries. The paper presents the dependence of the power increase ratio on the frequency and the pulse current duty ratio, which proves that the maximum possible output power of the hybrid storage system can be several times greater than the power of a single battery having the same parameters.